2014
DOI: 10.1093/nar/gku1304
|View full text |Cite
|
Sign up to set email alerts
|

Adhesin competence repressor (AdcR) from Streptococcus pyogenes controls adaptive responses to zinc limitation and contributes to virulence

Abstract: Altering zinc bioavailability to bacterial pathogens is a key component of host innate immunity. Thus, the ability to sense and adapt to the alterations in zinc concentrations is critical for bacterial survival and pathogenesis. To understand the adaptive responses of group A Streptococcus (GAS) to zinc limitation and its regulation by AdcR, we characterized gene regulation by AdcR. AdcR regulates the expression of 70 genes involved in zinc acquisition and virulence. Zinc-bound AdcR interacts with operator seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 59 publications
(94 reference statements)
4
85
0
Order By: Relevance
“…We have shown that the expression of the lmb, adcA, and adcAII genes is zinc dependent. Zn 2ϩ -dependent regulation is mediated in S. pneumoniae and S. pyogenes by the AdcR regulator (26,27,42). S. pneumoniae AdcR has a unique effector in zinc, and its crystal structure revealed the presence of two metal-binding sites (43).…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that the expression of the lmb, adcA, and adcAII genes is zinc dependent. Zn 2ϩ -dependent regulation is mediated in S. pneumoniae and S. pyogenes by the AdcR regulator (26,27,42). S. pneumoniae AdcR has a unique effector in zinc, and its crystal structure revealed the presence of two metal-binding sites (43).…”
Section: Resultsmentioning
confidence: 99%
“…GAS strains were grown in THY, and cells were harvested by centrifugation at either ME or early stationary (ES) phase of growth. RNA isolation, RNA purification, rRNA depletion, and the development of adapter-tagged cDNA libraries were performed as previously described (26). cDNA libraries were run on an Illumina HiSeq 2000 to obtain 51-bp reads, and the reads were subsequently mapped to the reference serotype M3 genome using the CLC Genomics Workbench, version 8 (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…The gene Spy_0124 (sloR), encoding a regulator involved in metal homeostasis, was also significantly upregulated by 10.3-fold in the fabT deletion mutant during mid-exponential phase at 35°C. Metalloregulators have been shown to modulate virulence gene expression in S. pyogenes (49)(50)(51).…”
Section: Identification Of Acquired Polymorphisms In Serotype M1 Stramentioning
confidence: 99%